Thyroid diseases in children and adolescents requiring surgical treatment—indications, techniques, results, and complications based on 10 years of the single center’s own experience - Sosnowska-Sienkiewicz, Patrycja; Danielewicz, Dajana; Januszkiewicz-Lewandowska, Danuta; Rusak, Paulina; Anderko, Iwona; Rzepecki, Maciej; Niedziela, Marek; Harasymczuk, Jerzy; Mańkowski, Przemysław (Frontiers in Endocrinology, 2024)
Introduction: Although thyroid abnormalities are observed less frequently in children than in adults, the increased incidence of thyroid cancer makes it mandatory for all pediatric surgeons to be knowledgeable about disorders of this gland. Thyroid abnormalities can be associated with hyperthyroidism or hypothyroidism and euthyroidism and/or symmetric or asymmetric enlargement of the gland. Aim: The present study was undertaken to retrospectively analyze the indications, surgical techniques used, results obtained, and complications found in the surgical treatment of thyroid diseases in children and adolescents in a surgical center for the macro-region of western Poland. Methods: The data of 148 patients undergoing total or partial thyroidectomy between 2013 and 2022 were analyzed from the medical records of the Department of Pediatric Surgery, Traumatology, and Urology of the Medical University of Poznan, Poland. Results: 95 children underwent subtotal and 64 total thyroidectomy, of which, in 45 patients, the procedure was widened to include prophylactic removal of neck lymph nodes. There were 113 girls (76%) in the analyzed group, and the average age of the patients at the time of surgical treatment was 15 years. The average time from the diagnosis of thyroid disease to surgery was 4 months, ranging from 2 weeks to 3 years. Of the 64 patients undergoing total thyroid resection, 35 (54.69%) were diagnosed with thyroid cancer. Conclusions: Collaboration within a multidisciplinary team ensures optimal surgical outcomes in children and adolescents with thyroid disease. With extreme caution, thyroid removal is a safe procedure with few complications, but the experience of the surgeon performing thyroid surgery in children remains crucial. Despite the absence of such a diagnosis in the first fine needle aspiration biopsy, the high percentage of thyroid carcinomas in the analyzed group may be because the initial biopsy was performed in a less experienced centre, also in terms of the histopathological laboratory. Hence, we point out the necessity of performing a repeat fine needle aspiration biopsy (according to the Bethesda classification) in a more experienced centre before the final decision of thyroidectomy.